Serum pregnancy-associated placental protein-a (PAPP-A) levels are increased in polycystic ovary syndrome (PCOS) in women with oligo-anovulation - Kılıç, Derya; Güler, Ömer Tolga (Journal of Surgery and Medicine, 2021)
Background/Aim: Pregnancy associated placental protein-A (PAPP-A) is a zinc-binding metalloproteinase with a key role in insulin like growth factor (IGF) pathway, and potential atherogenic effects. There is little information in the literature regarding PAPP-A levels in Polycystic ovary syndrome (PCOS). We aimed to investigate the serum PAPP-A levels among non-obese women with PCOS as a cardiovascular risk marker. Methods: Non-obese women of reproductive age (18-35 years of age) diagnosed with PCOS according to Rotterdam Consensus Conference criteria were included in this case-control study. Serum PAPP-A levels were compared with independent samples t-test between two main groups (PCOS and control) and investigated in PCOS subgroups as PCOS patients were further classified according to main phenotypes (hyperandrogenism and oligo-anovulation). Results: A total of 41 women with PCOS and 40 age- and body mass index- matched controls were included in the analysis. The serum PAPP-A levels of the control and PCOS groups, and of PCOS patients with hyperandrogenism were similar (P=0.128, P=0.261, respectively). However, the serum PAPP-A levels of those with oligo-anovulation was higher than those without (P=0.006), and that of women without oligo-anovulation was comparable to that of the control group (P=0.613). Conclusion: Lean and young PCOS women with oligo-anovulation had increased serum levels of PAPP-A when compared to women without. Prospective studies are needed to uncover the long-term cardiovascular risk of elevated PAPP-A levels in PCOS women with oligo-anovulation.